Dampak Penggunaan Gadget terhadap Kemampuan Interaksi Anak Sekolah Dasar pada Situasi Pandemi Covid-19’ - Al Ulil Amri, Muhammad Iqbal; Bahtiar, Reza Syehma; Pratiwi, Desi Eka (Trapsila: Jurnal Pendidikan Dasar, 2020)
The purpose of this article is to examine the impact of the use of gadgets for elementary school children and their benefit in a pandemic situation gadget covid-19. The design of this study uses literature review. The steps in the literature review are (1). Topic search; (2). Specify a title; (3). Conclusions. Writing analysis techniques in writing literature review are; (1). data collection; (2). data reduction; (3). drawing conclusions. In this writing, there is an analysis in the form of negative and positive impacts. Impact: The children can interact with your friends wherever you are, you can learn online through in pandemic covid-19 negative impact children more often play a gadget play from a friend about the environment so that children become individualisticKeyword :Gadget, Interaction Social, Primary School Children, Covid-19 Pandemic,